Health problems of cvilization (Termedia Publishing House, 2014)
Covering topics such as biomedical aspects of health, new diseases, physical activity or health-related behaviours. The mission of the journal is to popularize knowledge in the field of human health in the face of the dynamic changes in modern life caused by the development of civilization, industrialization, urbanization and environmental change. The accelerated progress in civilization (mainly industrialization, urbanization and environmental changes, new trends in diet and lifestyle as well as improvement in the quality of life) often affects human health negatively.